13 Reasons Why: Perceptions and Correlates of Media Influence in Psychiatrically Hospitalized Adolescents. Issue 1 (2nd January 2022) - Nesi, Jacqueline; Johnson, Sarah E.; Altemus, Melanie; Thibeau, Heather M.; Hunt, Jeffrey; Wolff, Jennifer C.
Abstract: Objective: The Netflix series 13 Reasons Why ( 13RW ) has sparked controversy due to graphic depictions of youth suicide, bullying, and sexual assault. However, further research is needed examining experiences of the show among youth with psychiatric illness. This exploratory, mixed-methods study examines adolescents' perceptions of 13RW and associations among viewership, suicide-related media influence processes, and self-injurious thoughts and behaviors (SITBs). Method: Participants were 242 adolescents hospitalized in a psychiatric inpatient facility; 60.7% female, 30.2% male, 9.1% other genders; ages 11 to 18; and 74.3% White, 7.5% Black, and 21.8% Hispanic. Participants completed measures of series viewership, media message processing, and SITBs. Participants who watched completed open-ended questions regarding beliefs and opinions about the series. Results: In all, 50.4% of participants watched 13RW, with girls (63.3%) more likely to have watched than boys (26.0%). More than half (55.9%) of youth expressed negative reactions to the show, while approximately one-third (33.8%) expressed positive reactions. Having watched the series was associated with greater likelihood of past-year non-suicidal self-injury (NSSI), but not with suicidal ideation or past-year suicide attempts. Youth's interpretation of media messages in 13RW, including greater identification with and perceived likeability of the main character, were associated with suicidal ideation and past-year NSSI. Conclusions: Findings suggest high rates of 13RW viewership among psychiatrically hospitalized youth, particularly girls, and provide insight into factors that may affect youths' vulnerability to suicide-related media effects.